Analisis Penerapan Good Corporate Governance Dalam Meningkatkan Kinerja Karyawan Pada Bank Syariah Indonesia Cabang Stabat - Mulya Anjani, Tira; Sani, Abdullah; Hasanah, Nurul (Universitas Muhammadiyah Sumatera Utara, 2023)
The implementation of Good Corporate Governance is carried out by taking into account aspects of employee performance, namely conducting training to improve employee skills functionally, training employees to work together as a team. Based on the results of the above observations, it can be seen that the implementation of Good Corporate Governance has been carried out properly by the Stabat Branch of Bank Syariah Indonesia. So, to describe the implementation of Good Corporate Governance in improving employee performance, the authors are interested in proposing a research title, namely